Morfologia de ionômero E/MMA-Na+ proposta por técnicas termo-ópticas - Gomez Higuita, German Dario (2017)
The DSC low temperature endothermic peak shown by sodium neutralized poly(ethylene-random-methacrylic acid) (E/MAA) ionomers has been shown here to be the result of two different and dependent morphological transformations, i.e. relaxation of the ionic aggregates and molecular reordering of ethylene chain segments. These two events could be separated by applying a hydrothermal treatment that swells the ionic clusters and allows the thickening the secondary PE crystals. Water plasticizes the ionic aggregates, shifting his glass transition temperature downwards. On the other hand the endothermic peak due to the molecular reordering of the thicker secondary crystals independently shifts upwards. The relaxation of the ionic aggregates was detected either by static (DSC) or dynamic (DMTA) thermal analysis. The reordering of ethylene segments were observed optically following the cross-polarized transmitted light intensity and by X-Ray diffraction pattern. Both, primary and secondary PE crystals, after either dry or wet thermal annealing improve the PE chains packing by expelling out the non-crystallizable methacrylic comonomer mers.